Clinical value to quantitate hematogones in Chinese childhood acute lymphoblastic leukemia by flow cytometry analysis. (16th March 2016) - Wang, Y.; Peng, L.; Dai, Q.; Ye, L.; Chen, L.; Chen, Q.; Lai, C.; Jiang, Y.; Zhang, G.
Summary: Introduction: Past studies have shown hematogones (HGs) become prominent in recovery phase after chemotherapy or hematopoietic stem cell transplantation, but still need further researches including different age, centers, and races to prove. So we provide relevant information regarding the clinical impact of this methodology in monitoring the response to treatment. Methods: HGs in 279 consecutive ALL patients at a time frame of postconsolidation treatment were recorded by flow cytometric minimal residual disease techniques according to the European BIOMED‐1 standard. Patients divided by risk stratification, clinical phases and cytogenesis test were judged. Results: Total HGs correlated inversely with age but not with >2 years, significant difference existed between ≤2 years and >2 years. HGs in low‐risk patients were much higher than that in intermediate‐ and high‐risk patients ( P < 0.01), significant difference ( P < 0.05) was also found for HGs quantitation between patients experiencing hematological complete remission and relapse. Total HGs and Pro‐B+immature B HGs in patients with TEL‐AML1 were much higher than those with BCR‐ABL and MLL‐AF4 ( P < 0.01). HGs > 1% of TNCs had significantly prolonged event‐free survival (EFS) ( P < 0.01); Multivariate analysis indicated HGs was independently associated with the longer EFS. Conclusion: The strong independently prognostic impact indicated that the better HGs regeneration is a marker of better response to therapy.